Policy Analysis Of Driving Schools And Their Impact On Education Financing - Rusdiman AB; Wanapri Pangaribuan; Syamsul Arif; Selamat Triono Ahmad (CV. AFDIFAL MAJU BERKAH, 2022)
Driving School is a school that focuses on developing student learning outcomes holistically by realizing the Pancasila Student Profile which includes competence and character starting with superior human resources (principals and teachers). The Motivating School Program is a refinement of the previous school transformation program. The Motivating School Program will accelerate public/private schools in all school conditions to move 1-2 stages further. The program is carried out in stages and is integrated with the ecosystem until all schools in Indonesia become the Motivating School Program. The first batch of the Driving School Program (PSP) for the 2021/2022 academic year has already started. There are 2,500 schools selected from 111 city districts that run the program. The Driving School Implementing School can inspire other schools to take part in the Mobilizing School Program. Motivating School teacher mentoring program. Initially the target was 61,000 people, now it is 23,145 people, with the budget dropping from Rp. 389.3 billion to Rp. 247.7 billion. Likewise with disaster-safe education units. The target is to decrease from 1,530 institutions to 1,290 institutions, with the budget falling from Rp. 152.1 billion to Rp. 115.9 billion.